1985
DOI: 10.1067/mva.1985.avs0020757
|View full text |Cite
|
Sign up to set email alerts
|

Celiac artery aneurysms: Historic (1745-1949) versus contemporary (1950-1984) differences in etiology and clinical importance

Abstract: Celiac artery aneurysms were encountered in nine patients, ranging in age from 39 to 76 years, at the University of Michigan Medical Center between 1961 and 1983. Developmental defects and atherosclerosis were etiologic factors in six cases. Four patients were without symptoms, whereas five experienced abdominal pain, including one with a ruptured aneurysm. Eight patients were subjected to surgical treatment; no deaths occurred and symptoms were resolved in all patients. A literature review of 108 celiac arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
1
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 0 publications
0
61
1
3
Order By: Relevance
“…Aneurysm involving splenic artery accounts approximately 6% of all visceral aneurysms while SMA is involved in the pathological process in 5.5% of cases [9]. Aneurysms of the common trunk of splenic and mesenteric arteries are very rare.…”
Section: Splenomesenteric Trunkmentioning
confidence: 99%
See 1 more Smart Citation
“…Aneurysm involving splenic artery accounts approximately 6% of all visceral aneurysms while SMA is involved in the pathological process in 5.5% of cases [9]. Aneurysms of the common trunk of splenic and mesenteric arteries are very rare.…”
Section: Splenomesenteric Trunkmentioning
confidence: 99%
“…Raptures of the splanchnic aneurysms occur in 20-22% of patients and result in enormous hemorrhage with mortality rate ranging from 35% to 100% [4,9,26,31].…”
Section: Introductionmentioning
confidence: 99%
“…However, Graham et al reported that in their experience the risk of rupture was only 13% [16]. Surgery has also been recommended for arterial aneurysm due to dissection in previous reports.…”
Section: Discussionmentioning
confidence: 97%
“…The surgical mortality rate in the latter era was 5.3%. 4 Open surgery is the usual choice for treating celiac aneurysms. Saphenous vein bypass from the supraceliac aorta to the hepatic and splenic arteries was used at our institution to treat a patient with celiac aneurysm.…”
Section: Discussionmentioning
confidence: 99%